A novel polysaccharide from mycelia of cultured Phellinus linteus displays antitumor activity through apoptosis. (25th June 2015) - Mei, Yuxia; Zhu, Hai; Hu, Qiming; Liu, Yangyang; Zhao, Shumiao; Peng, Nan; Liang, Yunxiang
Highlights: PLPS-1 and -2 were purified from mycelia of Phellinus linteus . The structures of the two polysaccharides were elucidated to be quite different. Only PLPS-1 displayed anti-proliferative effect against S-180 cells. PLPS-1 induced apoptosis of S-180 cells in a dose-dependent manner. The difference in antitumor activity results from the structural differences. Abstract: Two novel polysaccharides termed PLPS-1 and PLPS-2 were isolated from mycelia of cultured Phellinus linteus by hot water extraction, purified by DEAE-52 cellulose and Sephadex G-100 column chromatography, and structurally characterized by FTIR and NMR spectroscopy, GC–MS, periodate oxidation/Smith degradation, and methylation analysis. The monosaccharide compositions of PLPS-1 (MW 2.5 × 10 5  Da) and PLPS-2 (MW 2.8 × 10 4  Da) were respectively Glc, Ara, Fuc, Gal, and Xyl in molar ratio 21.964:1.336:1.182:1:1, and Glc, Gal, Man, Ara, Fuc, Xyl in molar ratio 14.368:2.594:1.956:1.552:1.466:1; i.e., both were heteropolysaccharides. The backbone of PLPS-1 consisted primarily of repeating α-d -Glc(1 → 4)-α-d -Glc(1 → 6) units, while that of PLPS-2 consisted of α-(1 → 3)-d -Glc and α-(1 → 6)-d -Glc. The side branches were also different in their carbohydrate components. In in vitro antitumor assays, PLPS-1 displayed strong anti-proliferative effect against S-180 sarcoma cells through apoptosis, whereas PLPS-2 had no such effect. The difference in antitumor activity between the two PLPS evidently results from their structural differences. PLPS-1 has potential as a novel anticancer agent.